Analysis of the profile of pregnant adolescents of a community in Recife-PE - Oliveira, Sheyla Costa de (2011)
The aim of this study was to analyze the profile of pregnant adolescents in a community in Recife. It was a quantitative study with descriptive approach and cross-sectional outline. It was performed with 17 adolescents of a community in Recife. Data collection was made by an instrument of objective questions, from May 2009 to May 2010. We found a rate for pregnancy of 3.82%; the average age was 16 years; 13 lived in consensual union; 07 had family income up to minimum wage (R$ 510.00); 14 were primigravidae; 08 had urinary tract infection and low weight, and 07 had anemia. It was considered that the pregnant adolescents were at a social and obstetric risk, which can cause negative results to their health. However, it is recommended greater attention to this population through damage reduction strategies for maternal health.